Edukasi Perawatan Mandiri Diabetes Melitus terhadap Pola Perawatan Mandiri dan Kontrol Gula Darah pada Pasien Rawat Jalan di RSU Imelda Pekerja Indonesia Medan - Purba, Lamtiur; Handoko, Sahrul; Gultom, Satriani H.; Damanik, Candra Meriani; Harahap, Ali Asman; Ritonga, Yuni Santi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Diabetes prevalence rate of 10.6%. Diabetics who do not carry out self-care have uncontrolled blood sugar levels. The purpose of activity is to see how the DM Self-Care Education Program influences the self-care behavior of DM patients and blood sugar levels at the Imelda Pekerja Indonesia Hospital. The implementation method of this Community Service Program is in the form of education and counseling.The implementation of this Program is divided into activity preparation, activity implementation and evaluation. The results of Program show that there is a significant difference in the self-care patterns of DM patients and  blood sugar levels of  DM patients before and after participating in the DM Self-Care Education Program. There are benefits of intervention in the description of self-care patterns before and after implementing program, with a p-value of 0.000.05, and in the description of blood sugar levels before and after implementation, p-value is 0.00-0.05. The Self-Care Education Program with DSME intervention provides encouragement for self-care awareness and blood sugar treatment.